2020
DOI: 10.1038/s41372-020-0614-4
|View full text |Cite
|
Sign up to set email alerts
|

Medications and in-hospital outcomes in infants born at 22–24 weeks of gestation

Abstract: Objective-To evaluate the most commonly used medications and in-hospital morbidities and mortality in infants born 22-24 weeks of gestation. Study design-Multicenter retrospective cohort study of infants born 22-24 weeks of gestation (2006-2016), without major congenital anomalies and with available medication data obtained from neonatal intensive care units managed by the Pediatrix Medical Group. Results-This study included 7578 infants from 195 sites. Median (25th, 75th percentile): birthweight was 610 g (54… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 52 publications
0
16
0
Order By: Relevance
“…The survival rate of periviable infants varies greatly between studies and countries [ 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. Although the related ethics issues are under debate, aggressive treatments improve the survival rate of periviable infants, especially those born at 22–23 weeks GA [ 7 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The survival rate of periviable infants varies greatly between studies and countries [ 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. Although the related ethics issues are under debate, aggressive treatments improve the survival rate of periviable infants, especially those born at 22–23 weeks GA [ 7 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Periviable birth is defined as delivery happening from 20 0/7 to 25 6/7 weeks gestational age (wGA) [ 4 , 5 , 6 ]. In the past two decades, there have been reports of increased rates of survival of periviable infants born at 22–25 wGA from single centers or large cohorts in Taiwan, Japan, USA, France, Germany, and Australia [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. However, the reported survival rate of periviable infants varied between reports (49.7–86.2%) [ 9 , 11 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thirty-four of 60 studies reported the proportion of preterm infants (born at <37 weeks gestational age) among their cohort (range 20% [24] to 87% [71]) in addition to the two studies (34), (31) that included preterm infants only. In addition, one study Puia-Dumitrescu 2020 [72] reported drugs received by infants born at 22-24 weeks gestational age only.…”
Section: Number Of Drugs Per Infantmentioning
confidence: 99%
“…North America (10 studies) [8,9,28,38,53,60,69,70,72,78] ampicillin (8 studies), gentamicin (8 studies), furosemide (6 studies), surfactant (6 studies), penicillin (5 studies), vancomycin (6 studies), caffeine citrate* (6 studies), cefotaxime (4 studies), dopamine (5 studies), calcium gluconate (4 studies) Asia (6 studies) [14,17,19,51,55,73] phenobarbitone (4 studies), vitamin K (4 studies), amikacin (3 studies), aminophylline (3 studies), ceftriaxone (2 studies), ceftazidime (2 studies), gentamicin (2 studies), phenytoin (2 studies), penicillin/sulbactam (2 studies),caffeine (1 study) Latin America and Caribbean (4 studies) [15,24,32,41] fentanyl (4 studies), gentamicin (3 studies), vancomycin (3 studies), multivitamins (3 studies), amikacin (2 studies), ampicillin (2 studies), furosemide (2 studies), aminophylline (2 studies), morphine (1 study), metamizole (1 study)…”
Section: Geographic Region (Number Of Studies) (Ref) Most Frequently mentioning
confidence: 99%
“…The U.S. FDA experience with drug development in neonates is minimal; of 301 pediatric drug development programs reviewed in 2015, only 26 included neonatal labeling, and only 8 drugs had studies that contained sufficient neonate data to support population PK (POPPK) analysis in this age group 4 . In 2021, clinical trial networks like the Pediatric Trials Network continue to make progress in informing pediatric labeling for the understudied neonatal populations 5–11 …”
mentioning
confidence: 99%